2023
DOI: 10.1017/dmp.2023.10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implementing and Lifting COVID-19 Lockdown on Study and Physical Activity Patterns Among Youths in China

Abstract: Introduction The youths’ study and physical activity (PA) patterns may have been affected by lockdown measures due to COVID-19. This study aimed to reveal how youths’ study and PA patterns had changed after implementing and lifting COVID-19 lockdown in China. Methods The COVID-19 Impact on Lifestyle Change Survey (COINLICS) was used, where 10,082 youth participants have voluntarily reported their study and PA patterns in the three periods before, during, and after COVID-19 lockdown. PA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The outbreak of COVID-19 may further accelerate Internet use and its related problems in children and adolescents (11)(12)(13)(14). In January 2020, the Ministry of Education of China issued notices to postpone the opening of spring semester of all primary and secondary schools, and required students to stay at home and study through the Internet, which lasted for more than 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of COVID-19 may further accelerate Internet use and its related problems in children and adolescents (11)(12)(13)(14). In January 2020, the Ministry of Education of China issued notices to postpone the opening of spring semester of all primary and secondary schools, and required students to stay at home and study through the Internet, which lasted for more than 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the 20 studies, six studies focused on walking only (18,21,(33)(34)(35)(36), eight focused on cycling only (17,22,24,(37)(38)(39)(40)(41), and another six studies included both cycling and walking (23,(42)(43)(44)(45)(46). Bikesharing is a concerned research topic that five studies focused only on it (17,22,24,37,41), three of which were about dock-less bike-sharing (DBS) (17,22,37), one about station-based bike-sharing (SBBS) (24), and one about both kinds (41).…”
Section: Characteristics Of Existing Researchmentioning
confidence: 99%
“…Bikesharing is a concerned research topic that five studies focused only on it (17,22,24,37,41), three of which were about dock-less bike-sharing (DBS) (17,22,37), one about station-based bike-sharing (SBBS) (24), and one about both kinds (41). 13 studies focused on general urban residents (17,(22)(23)(24)(37)(38)(39)(40)(41)(42)(43)(44)(45), while another of seven studied specific research populations, like youths (33,35,36,46), middle-aged and older adult people (18,21) and disabled people (34). The earliest study was published in October 2020.…”
Section: Characteristics Of Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…One survey showed that 41.8 % of mothers felt that breastfeeding was protected by the lockdown, but 27.0 % said that the lockdown created many barriers to breastfeeding [ 11 ]. As the pathogenicity and lethality of Omicron declined and treatment improved steadily, the lockdown measures were lifted [ 12 , 13 ]. People infected with COVID-19 were no longer isolated centrally [ 14 ], which might increase the risk of people being exposed to the virus, especially nurses on the front line of the epidemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%